Water histories of south Asia : the materiality of liquescence - Ray, Sugata; Maddipati, Venugopal (Oxon : Routledge, 2020)
"This book surveys the intersections between water systems and the phenomenology of visual cultures in early Modern, colonial and contemporary South Asia. Bringing together contributions by eminent artists, architects, curators and scholars who explore the connections between the environmental and the cultural, the volume situates water in an expansive relational domain. It covers disciplines as diverse as literary studies, environmental humanities, sustainable design, urban planning and media Studies. The chapters explore the ways in which material cultures of water generate technological and aesthetic acts of envisioning geographies, and make an intervention within political, social and cultural discourses. A critical Interjection in the Sociologies of water in the subcontinent, the book brings art history into conversation with current debates on climate change by examining Water$1 (Bs artistic, architectural, engineering, religious, scientific and Environmental facets from the 16th century to the present. This is one of the first books on South Asia$1 (Bs art, architecture and visual history to interweave the ecological with the aesthetic under the emerging field of eco art history. The volume will be of interest to scholars and General readers of art history, Islamic studies, South Asian studies, urban studies, architecture, Geography, History and Environmental Studies. It will also appeal to activists, curators, art critics and those interested in water management."--s
Keywords: Water and civilization; Water -- Social aspects